Magnetic graphene oxide nanocomposites as an effective support for lactase immobilization with improved stability and enhanced photothermal enzymatic activity. (17th March 2021) - Li, Yinglong; Wang, Buchuan; Wu, Minjie; Huan, Weiwei; Li, Jie
Abstract : Magnetic graphene oxide-immobilized lactase with high loading capacity, improved stabilities, and photothermal enhancement of activity has been reported. Abstract : Development of an effective carrier for enzyme immobilization with improved stability and reusability is an attractive topic in enzyme chemistry. In this study, a magnetic graphene oxide (mGPP) nanocomposite is prepared and employed as a carrier for the immobilization of lactase to improve stability and reusability performances. The grafted polyethylenimine on mGPP nanocomposites provides abundant amino groups for bonding lactase and flexible arms for enhancing the enzyme activity. The resultant mGPP-Lactase possesses a loading capacity of 278.8 mg g −1, and improved stabilities under wide pH solutions and temperature conditions. Benefiting from the unique magnetic response property of the functional carrier, the mGPP-Lactase can be magnetically separated from the aqueous solution and rapidly recycled, maintaining its 83.1% activity even after 20 consecutive cycles. More importantly, the mGPP nanocomposite can generate heat under NIR light irradiation due to the photothermal effect, leading to the remarkable increase of solution temperature and further significant enhancement of enzyme activity (152% of the activity of free lactase). Moreover, the mGPP-Lactase demonstrates high performance in hydrolysis of milk lactose under NIR light irradiation. The magnetic graphene oxide-immobilized lactase has promising potential in cyclic hydrolysis processes in biocatalytic fields.